Tsunami Disaster Preparedness Simulation on North Buton Regency - Jajang Sanjaya (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Geographical location of North Buton Regency which directly opposite the Banda Sea and placed in the reverse fault of Makassar Strait, Matano fault, Lawanoppo, and Kolaka, which are tsunami-prone areas due to earthquake and submarine landslide. These then caused the area has high disaster risk, because of the settlement that is located on the seashore. Therefore, a study to understand the preparedness level of community in North Buton Regency in confronting the tsunami disaster is needed; in order to be able to determine the mitigation steps, also the effective evacuation route and location to minimize the casualties caused by tsunami. Kulisusu Sub-district is a territory with a fairly long coastal area, wherein the population density is the highest in North Buton Regency, this then made the area has high disaster risk. This research used questionnaire instrument to discover the preparedness level of the community, and the numerical simulation method with multi-agent system in the tsunami evacuation simulation. The conducted simulation did not specify the evacuation route or path, yet the agents were allowed to move freely to the shelter. The simulation was conducted at day and night time. The result of the research pointed on matter of preparedness level of community, in which factor of preparedness of the community in facing the disaster is very important, by the means of establishing simulation drill, preparing the controller officers, and managing the comfort on the shelter, such as strategic location and good position, also creating a good early warning system so that more residents could be saved.